Biosynthesized Silver Nanoparticles from Eruca sativa Miller Leaf Extract Exhibits Antibacterial, Antioxidant, Anti-Quorum-Sensing, Antibiofilm, and Anti-Metastatic Activities - Amir Mahgoub Awadelkareem; Eyad Al-Shammari; AbdElmoneim O. Elkhalifa; Mohd Adnan; Arif Jamal Siddiqui; Mitesh Patel; Mohammad Idreesh Khan; Khalid Mehmood; Fauzia Ashfaq; Riadh Badraoui; Syed Amir Ashraf (MDPI AG, 2022)
Worldwide, the primary problem today is the proliferation of cancer and secondary bacterial infections caused by biofilms, as they are the principal causes of death due to the lack of effective drugs. A great deal of biological activities of silver nanoparticles (AgNPs) have made them a brilliant choice for the development of new drugs in recent years. The present study was conducted to evaluate the anticancer, antibacterial, anti-QS, and antibiofilm effects of AgNPs synthesized from Eruca sativa (E. sativa) leaf extract. The ultraviolet-visible (UV-Vis) spectra showed a peak of surface plasmon resonance at 424 nm λmax, which corresponded to AgNP formation. The Fourier transform infrared spectroscopy (FT-IR) confirmed that biological moieties are involved for the development of AgNPs. Moreover, transmission electron microscopy (TEM) analyses confirmed the spherical shape and uniform size (8.11 to 15 nm) of the AgNPs. In human lung cancer cells (A549), the anticancer potential of AgNPs was examined by the MTT [3-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay, scratch assay, and invasion assay. The results indicated that AgNPs inhibit the migration of A549 cells. The synthesized AgNPs showed MIC values of 12.5 µg/mL against Chromobacterium violaceum (C. violaceum) and 25 µg/mL against Pseudomonas aeruginosa (P. aeruginosa), which demonstrated their antibacterial abilities. Biological compounds that disable the QS system are being investigated as potential strategies for preventing bacterial infections. Thus, we analyzed the potential effectiveness of synthesized AgNPs in inhibiting QS-regulated virulence factors and biofilm formation in both strains of bacteria. In C. violaceum, the synthesized AgNPs significantly inhibited both violacein (85.18% at 1/2 × MIC) and acyl homoserine lactone (78.76% at 1/2 × MIC). QS inhibitory activity was also demonstrated in P. aeruginosa at a sub-MIC concentration (1/2 × MIC) by a reduction in pyocyanin activity (68.83%), total protease (68.50%), LasA activity (63.91%), and LasB activity (56.40%). Additionally, the exopolysaccharide production was significantly reduced in both C. violaceum (65.79% at 1/2 × MIC) and P. aeruginosa (57.65% at 1/2 × MIC). The formation of biofilm was also significantly inhibited at 1/2 × MIC in C. violaceum (76.49%) and in P. aeruginosa (65.31%). Moreover, a GC-MS analysis confirmed the presence of different classes of bioactive phytochemical constituents present in the leaf extract of E. sativa. On the basis of our results, we conclude that biologically synthesized AgNPs showed numerous multifunctional properties and have the potential to be used against human cancer and bacterial biofilm-related infections.